INFLUENCE OF DIGITAL TRANSFORMATION ON SUZUKI DEALER’S PERFORMANCE THROUGH INNOVATION AS INTERVENING VARIABLE - Partogi Soloan Samosir (Krisnadwipayana International Journal of Management Studies, 2022)
he purpose of thus study was to determine the effect of digital transformation and innovasionon Suzuki automotive Dealers in Indonesia. Digital transformation is a trend and a necessity to survive inthe current pandemic era. Automotive dealer as apart of automotive industry as one of the industries thatis required to be very responsive and fundamental in nature also needs to carry out digital transformation.The research method used is descriptive qualitative and quantitatives analysis. The analysis model usedSPSS. The population in this study were 51 Suzuki dealers in Indonesia, with sample 42 dealers. Based ondata analysis known that Digital Transformation affect the Performance of Suzuki Dealers partially, DigitalTransformation affect the Innovation partially, and Innovation affect the Performance of SuzukiDealerspartially. But in this case Innovation can’t provide improved between Digital Transformation andSuzuki Dealers Performance